The PTIMIZING THE IMPLEMENTATION OF LEARNING STRATEGIES LIMITED FEATURES TO CLASS V STUDENTS AT SDN 1 BANYUSRI, BOYOLALI REGENCY: PTIMIZING THE IMPLEMENTATION OF LEARNING STRATEGIES LIMITED FEATURES TO CLASS V STUDENTS AT SDN 1 BANYUSRI, BOYOLALI REGENCY - siti (Program Studi Bimbingan dan Konseling FKIP Universitas Slamet Riyadi, 2022)
ABSTRACTThe author performs the actualization and habituation with the aim of applying the basic values ​​of civil servants (BerAKHLAK) namely Service Oriented, Accountable, Competent, Harmonious, Loyal, Adaptive and Collaborative. In addition, it is to implement the position and role of civil servants to support the realization of Smart Governance, namely Management ASN and SMART ASN. This actualization activity is carried out from April 9 to June 8, 2022 by applying the basic values ​​of civil servants, including Service Oriented, Accountable, Harmonious, Loyal, Adaptive and Collaborative as well as carrying out activities based on the position and role of civil servants, including Management ASN and SMART ASN.The actualization and habituation activity with the title: